Biological, ecological, morphological and cytogenetic analyses, with taxonomic notes of Zelurus ochripennis (Stål, 1854) (Hemiptera: Heteroptera: Reduviidae: Reduviinae) - Oliveira, Jader; Alevi, Kaio Cesar Chaboli; Gil-Santana, Hélcio R.; Galvão, Cleber (Zootaxa, 2021)
Based on specimens of Zelurus ochripennis (Stål, 1854) collected in the entrance zone of a small terrestrial cave, some biological, ecological, morphological and cytogenetic data, as well, as the general morphology of their nymphs are presented for the first time. A short taxonomic summary of the species is also provided.